Bifurcations in model gause predator - prey with discontinuity - Cortés-García, Christian (2021)
This paper presents the necessary conditions to guarantee the existence of a stable limit cycle in a predator - prey model and some geometrical aspects to perform a qualitative analysis in two - dimensional Filippov dynamic systems. With these defined guidelines, the dynamics of a predator - prey model are studied when exploitation in predators is restricted if the number of prey is lower than a critical value. The study is carried out by the bifurcation analysis in relation to two parameters: exploitation and protection of the populations to interact.